1994
DOI: 10.1046/j.1365-2532.1994.1120082.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs for health information: a literature review

Abstract: This paper explores the recent literature on unmet needs for health information, giving an overview of some of the research that has been carried out since Kempson's review and study in 1987. Many of the studies looking at health information needs have been approached from a narrow focus of individual information needs for specific services, with limited research into the views of the general public. The greatest demand for health information appears to be in the area of specific diseases and medical condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Lay interpersonal sources of health-related information People receive quite a lot of health-related information informally, often without any active performance of themselves, by lay interpersonal sources of information, such as the close family, other kin, friends and workmates (Buckland, 1994;Ek, 2005;Ford and Kaphingst, 2009). In fact, it has been suggested that the most used information sources for most people are kin and peer relations (Dervin, 1983;Chatman, 1996); that is, people meet, communicate and give and ask advice from people in their everyday life networks.…”
Section: Interest In Health Information and Health Information Seekinmentioning
confidence: 99%
“…Lay interpersonal sources of health-related information People receive quite a lot of health-related information informally, often without any active performance of themselves, by lay interpersonal sources of information, such as the close family, other kin, friends and workmates (Buckland, 1994;Ek, 2005;Ford and Kaphingst, 2009). In fact, it has been suggested that the most used information sources for most people are kin and peer relations (Dervin, 1983;Chatman, 1996); that is, people meet, communicate and give and ask advice from people in their everyday life networks.…”
Section: Interest In Health Information and Health Information Seekinmentioning
confidence: 99%
“…Prior research has assessed cancer information seeking. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Furthermore, specific evaluation of the information sought by callers to the CIS has also been pursued 7,[17][18][19][20][21][22][23][24][25] ; however, many of these prior evaluations have examined the information sought by cancer patients 6,17,18,21,23 and their caregivers. 17,19 Growing public interest in cancer information coupled with increases in the amount and complexity of cancer information demands careful, timely, and continual evaluation of public requests for information.…”
mentioning
confidence: 99%
“…At different stages of health and illness, consumers have different levels of needs and require different types of information [5]. The study identified eight stages on which general users could search for health information: when healthy, when they think they might be ill, before getting a medical test, when diagnosed as ill, before treatment, when receiving the treatment, after treatment/surgery, and when being chronically ill. At different stages, people had different foci of concern and asked for different types of information.…”
Section: Discussionmentioning
confidence: 99%
“…Askers felt that they did not get enough information from healthcare professionals (5). Some askers reported that MDs or nurses refused to discuss with them issues of interest, had not told them much, could not seem to find what it was, or simply shrugged their questions off.…”
Section: Cognitive Motivationsmentioning
confidence: 99%